2019
DOI: 10.1038/s41586-018-0832-5
|View full text |Cite|
|
Sign up to set email alerts
|

GABAA receptor signalling mechanisms revealed by structural pharmacology

Abstract: Summary Type-A γ-aminobutyric receptors (GABA A Rs) are ligand-gated chloride channels with a very rich pharmacology. Some of their modulators, including benzodiazepines and general anaesthetics, are among the most successful drugs in clinical use and common substances of abuse. Without reliable structural data, the mechanistic basis for pharmacological modulation of GABA A Rs remains largely unknown. Here we report high-resolution cryoEM structures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
545
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(593 citation statements)
references
References 69 publications
42
545
0
6
Order By: Relevance
“…Icilin/Ion channel TRPM8 (PDB:6NR3, EMD:0487) 41 ; LY2119620/M2R (PDB:6OIK, EMD:20079) 38 ; Iperoxo/M2R (PDB:6OIK, EMD:20079) 38 ; Saxitoxin/Nav1.7 (PDB: 6J8G, EMD:9781) 39 ; Biculine/GABAA (PDB:6HUK, EMD:0280) 37 ; Xanax/GABAA (PDB:6HUO, EMD:0282) 37 ; Valium, GABAA (PDB:6HUP, EMD:0283) 37 ; NDI-091143/ATP Citrate Lyase (PDB:6O0H, EMD:0567) 7 ; paroxetine/serotonin transporter (PDB:6DZW, EMD:8941) 40 ;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Icilin/Ion channel TRPM8 (PDB:6NR3, EMD:0487) 41 ; LY2119620/M2R (PDB:6OIK, EMD:20079) 38 ; Iperoxo/M2R (PDB:6OIK, EMD:20079) 38 ; Saxitoxin/Nav1.7 (PDB: 6J8G, EMD:9781) 39 ; Biculine/GABAA (PDB:6HUK, EMD:0280) 37 ; Xanax/GABAA (PDB:6HUO, EMD:0282) 37 ; Valium, GABAA (PDB:6HUP, EMD:0283) 37 ; NDI-091143/ATP Citrate Lyase (PDB:6O0H, EMD:0567) 7 ; paroxetine/serotonin transporter (PDB:6DZW, EMD:8941) 40 ;…”
Section: Methodsmentioning
confidence: 99%
“…Using GlideEM we were able to identify candidate poses in this resolution range with cross correlations that were comparable to the deposited poses for all of the structures that we studied. For GABAA in complex with three different ligands 37 , the M2 muscarinic acetylcholine receptor in complex with two different ligands 38 , the sodium channel Nav1.7 with one ligand 39 , ATP citrate lyase with one ligand 7 , and the serotonin transporter with two different ligands 40 the poses we identified with GlideEM largely agreed with what was deposited in the PDB ( Supplementary Fig. 7) (although it should be noted that for the deposited structures of the M2 receptor and serotonin transporter the ligands were docked with the traditional version of Glide).…”
Section: Using Gemspot With 30-45 å Resolution Mapsmentioning
confidence: 99%
“…We observed that the variant was in a highly conserved residue and the radius of the pore was narrowed at the gate in both closed and desensitized structures of the receptor. Having a residue like proline with a rigid side chain (or an alanine like in the β subunits with a non-rigid but very small side chain) at the intracellular -2' position allows tight control of the gating upon neurotransmitter extracellular binding, exerting rigid body motion of the TMH, as can be observed in recent GABAA and Gly receptors structures (26)(27)(28)51). Replacing the constraining proline with a leucine will permit changes in the backbone conformation (52).…”
Section: Discussionmentioning
confidence: 99%
“…It is near the Thr264, which interacts with the Thr292 (where the mutation Thr292Lys is) ( Figure 2B,D). Met263 is also part of the recently reported low affinity binding site for benzodiazepines, a group of sedative anticonvulsant drugs (28)(29)(30). In the desensitized GABAA α1β3γ2 receptor bound to Diazepam (DZP), Met263 is part of the opening of the pocket to the external molecular surface and its lateral chain sulfur establishes direct interaction with the diazepine ring of DZP (Supp.…”
Section: Structural Characterization Of the Novel And Previously Repomentioning
confidence: 99%
“…[8,9] Transport is regulated by controlling the opening and closing of channels (gating)i nr esponse to diverse stimuli, including changes in membrane potential, ligand binding or mechanical force. [10][11][12][13][14][15][16][17] Furthermore, the structural asymmetry observed in rectifying ion channels Ak ey conundrum in the constructiono fa na rtificial cell is to simultaneously maintain ar obust physical barriert ot he external environment, while also providing efficient exchange of informationa cross this barrier.B iomimicry provides an umber of avenues by which such requirementsm ight be met. Herein, we provide ab rief introductiont ot he challenges facing this field and explore progress to date.…”
Section: Ion Channelsmentioning
confidence: 99%